Resistance to fracture of endodontically treated teeth: Influence of the post systems and cements - De Matos, Luanne; Oliveira, Lucas [UNESP]; Silva, Aryvelto [UNESP]; Silva, Jessica [UNESP]; Silva, Marcelo (Wolters Kluwer, 2020)
Background: Endodontically treated teeth with extensive structural damage present higher fragility due to the low amount and worse quality of the reminiscent tissues of the crown. Materials and Methods: The present in vitro study evaluated the effect of different intraradicular retainers and cementation agents on the fracture resistance of devitalized teeth. Incisive teeth (n = 40) of bovine mandibles were used. After preparation of the root canals, they were immersed in polyether, in a polyvinyl chloride cylinder containing acrylic resin, to simulate the periodontal ligament. The specimens were randomly divided into four groups (n = 10), according to the type of retainer (anatomical or main with accessory posts) and resin cement used (conventional resin cement-RelyX ARC or self-adhesive resin cement-RelyX U200). The specimens were stored in distilled water at 37°C and submitted to fracture resistance testing. ANOVA and Tukey's test were applied for data analysis, with significance level set at 5%. Results: There was no interaction between cement type and intraradicular retainers (P = 0.56) or even between the types of cement used (P = 0.65). However, in the variation of the types of retainers, the group using main with accessory posts presented greater resistance to the fracture than the anatomical post (P = 0.04). Conclusion: Different cementing agents have no effect on the fracture strength of devitalized teeth, unlike the use of posts, in which the use of accessory post proved more resistant when compared to the anatomical post.
Keywords: Dental cements; dental pins; tooth fractures